Optical shaping of gas targets for laser plasma ion sources - Dover,N; Cook,N; Tresca,O; Ettlinger,O; Maharjan,C; Polyanskiy,M; Shkolnikov,P; Pogorelsky,I; Najmudin,Z (Journal of Plasma Physics, 2016)
We report on the experimental demonstration of a technique to generate steep densitygradients in gas jet targets of interest to laser plasma ion acceleration. By using anintentional low energy prepulse, we generated a hydrodynamic blast wave in the gas toshape the target prior to the arrival of an intense CO2 (λ ≈ 10 µm) drive pulse. Thistechnique has been recently shown to facilitate the generation of ion beams by shockwaveacceleration (Tresca et al. 2015). Here, we discuss and introduce a model to understandthe generation of these blast waves and discuss in depth the experimental realisationof the technique, supported by hydrodynamics simulations. With appropriate prepulseenergy and timing, this blast wave can generate steepened density gradients as short asl ≈ 20 µm (1/e), opening up new possibilities for laser-plasma studies with near-criticalgaseous targets.